(untitled) - The World Bank (Hanoi, 2006)
This report on telecommunications Strategy - Current Status and Future paths is one of six volumes dealing with Vietnam's infrastruture challenge. The reports have been revised to take account of comments made by the government in workshops during May 15-17, 2006. The comments of numerous colleagues from the World Bank, Asian Development Bank, and the Japan Bank for International Cooperation are gratefully acknowledged.
Keywords: Telecommunication systems